(untitled) (Bangladesh Journal of Botany, 2008)
Laboratory experiments were conducted to study the effect of salt solution, and size and ageing of seeds on growth efficiency of rice seedlings. Variation in growth efficiency due to different factors was significant. Seeds of Pokkali, BRRI dhan 29, BRRI dhan 40 and BRRI dhan 41 rice genotypes were used. Growth efficiency and other seedling characteristics decreased as salinity levels increased. Three varieties of rice BR 14, BRRI dhan 28 and BR 1, which are large, medium and small grain variety, respectively, were used to study the effect of seed size on growth efficiency and seedling growth. All the parameters decreased remarkably with decreasing seed size. Seed size influenced the growth efficiency significantly. For accelerated ageing test five varieties of freshly harvested seeds were used. The tested varieties responded differently for growth efficiency. When the ageing treatments were extended to 72 hours the growth efficiency depressed markedly for most of the varieties. Key words: Growth efficiency, Ageing, Rice, Salt solution, Seedling growth, Seed size DOI = 10.3329/bjb.v36i2.1508 Bangladesh J. Bot. 36(2): 171-176, 2007 (December)